Native valve endocarditis caused by corynebacterium striatum with heterogeneous high-level daptomycin resistance: collateral damage from daptomycin therapy? (2012)
We describe a patient who developed Corynebacterium striatum native valve endocarditis after receiving two 6-week courses of daptomycin for the treatment of methicillin-resistant Staphylococcus aureus bacteremia and osteomyelitis. The organism exhibited in vitro heteroresistance to daptomycin, with two subpopulations showing daptomycin susceptibility (MIC of ≤0.094 μg/ml) and high-level resistance to daptomycin (MIC of ≥256 μg/ml). The selection of daptomycin-resistant Gram-positive skin flora with the potential of causing invasive disease may be a concern during prolonged courses of daptomycin.